2023
DOI: 10.3390/plants12233937
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fulvic Acid on Growth and Nitrogen Utilization Efficiency in M9T337 Seedlings

Bo Yu,
Laiping Wang,
Dongdong Cui
et al.

Abstract: Both fulvic acid (FA) and nitrogen (N) play important roles in agricultural production in China. Plants typically show a higher nitrogen utilization efficiency (NUE) under FA application. However, the role of FA application in apple growth and NUE remains unclear. A hydroponic culture experiment was performed, and M9T337 seedlings (a dwarf apple rootstock) were used as the experimental subjects. The biomass, photosynthesis, accumulation, and distribution of photosynthates, N absorption and assimilation, and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Total RNA was extracted from 0.1 g of the roots using the RNAiso Plus extraction kit (Takara, Otsu, Shiga, Japan). Subsequently, RNA extraction, reverse transcription, and qRT-PCR procedures followed a previously reported procedure ( Yu et al., 2023a ). The relative gene expression levels were normalized according to the 2 –ΔΔCT method, and the MdActin gene was used as the internal reference gene.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was extracted from 0.1 g of the roots using the RNAiso Plus extraction kit (Takara, Otsu, Shiga, Japan). Subsequently, RNA extraction, reverse transcription, and qRT-PCR procedures followed a previously reported procedure ( Yu et al., 2023a ). The relative gene expression levels were normalized according to the 2 –ΔΔCT method, and the MdActin gene was used as the internal reference gene.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is very important to maintain C and N assimilation homeostasis to mitigate the inhibitory effects of external stress conditions on plant growth ( Ren et al, 2021 ). Although numerous studies have shown that FA application could promote plant growth through the regulation of C and N metabolism ( Gao et al., 2022 ; Yu et al., 2023a ), details regarding the effects of Cd stress on C and N metabolism in apple plants and whether FA is sufficient to mitigate the inhibitory effects of Cd stress on apple plants growth, from the perspective of the regulation of C and N metabolism, both remain unclear.…”
Section: Introductionmentioning
confidence: 99%